The relationship between weekly instruction, homework time and students’ competences. - López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (Sage, 2025)
Students’ use of learning time both inside and outside of school has been at the core of education debates for many years, although evidence is still mixed. Particularly, in order to analyse the contribution of the time students use for learning to their competences, we use TIMSS 2019 data for a total of 276,512 fourth grade students in 58 countries. Taking advantage of the information by subject provided in this dataset, we go beyond correlation analysis by using student fixed-effects. Our results show that one additional hour of weekly instruction and homework times have a non-significant influence on students’ competences in most of the analysed countries, while they also present a low positive influence in some of them. This may suggest the need of re-orienting school instruction and homework times following the education curriculum model of those countries in which the influence is positive, so students can improve their skills.
https://openpolicyfinder.jisc.ac.uk/id/publication/9519
Keywords: Ciencias - Estudio y enseñanza; Deberes escolares en casa; Educación - Modelos matemáticos; Weekly instruction time; Weekly homework time; Student fixed-effects; TIMSS; Fourth grade